Marketing Communications Strategy In The Process Of Commercialization Of Innovative Products Start-Up Company "Mobilmantan.id” - Sary, Kezia Arum; Achmad, Gusti Noorlitaria; Yuni, Yuni; Leilani, Adelia; Warohma, Syaqinah Shiva (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The start-up company mobilmantan.id’s marketing communications strategy for bringing innovative products to market is the subject of this study. The company wants to effectively engage investors, and customers, and conduct market research by utilizing channels like crowdsourcing, pitching, networking, and social media. The research employs a literature review method with a qualitative approach to explore the complexities of innovation commercialization, which involves transforming innovations into marketable products through substantial financial investment and risk. Drawing from a comprehensive analysis of 194 articles across 62 journals, a framework outlining the innovation commercialization process has been developed, highlighting three main phases: discovery, development, and implementation. Analyzing the company's approach to marketing communications and its effect on the commercialization process were the initial methods. According to the findings, using digital channels and third-party collaborations significantly increased sales and customer engagement. Throughout the process, difficulties like establishing credibility, acquiring patents, and running out of funds were identified and addressed. The study concludes that during the commercialization process, effective marketing communications are crucial in increasing product awareness and sales. While impediments in example size and generalizability exist, the exploration offers important bits of knowledge for new businesses exploring the intricacies of development commercialization.